The Prognostic Significance of Collagen VI in Pancreatic Ductal Adenocarcinoma - Kesti, Ella; Borgmästars, Emmy; Hagström, Jaana; Mustonen, Harri; Seppänen, Hanna; Haglund, Caj; Sund, Malin (Ovid Technologies (Wolters Kluwer Health), 2025)
Objectives: Pancreatic ductal adenocarcinoma (PDAC) is characterized by poor prognosis and lack of biomarkers. A rich desmoplastic tumor stroma is considered a hallmark of PDAC and previous studies have indicated upregulated expression of collagen VI (COL6) in PDAC. COL6 is shown to associate with prognosis in many cancers but has been less extensively studied in PDAC.
Materials and methods: The expression of COL6 was analyzed by immunohistochemistry in tissue microarrays containing resected tumor tissue samples from PDAC patients (n = 164). Significance of COL6 was estimated with Kaplan-Meier survival estimates and multivariable Cox regression analysis. COL6 protein and mRNA expression patterns were further investigated in publicly available datasets.
Results: There were no statistically significant ( P < 0.05) differences in survival when comparing high and low protein expression of any of the analyzed COL6 α-chains (α1(VI): hazard ratio [HR] 0.90, 95% confidence interval [CI] 0.64-1.28; α2(VI): HR 1.28, 95% CI 0.86-1.89; α3(VI): HR 0.91, 95% CI 0.64-1.29). Similar results were obtained when assessing public data from the Cancer Proteome Atlas, Clinical Proteomic Tumor Analysis Consortium, and The Cancer Genome Atlas.
Conclusions: In contrast with previous studies and some other cancers, we did not find any association of COL6 tissue expression and PDAC survival.